Zakat Profesi Antara Pendukung dan Penentangnya - Ali Trigiyatno (Jurnal Hukum Islam, 2016)
Zakah of profession is one source of zakat which began intensively conducted by the government through BAZNAS and Islamic mass organizations in Indonesia recently. Nevertheless, a group of scholars and Islamic mass organizations apparently still has not fully accepted the obligation of this zakah. With other languages,zakah profession still has proponents and opponents. Supporters of zakah of profession consists of MUI, Government, NU, Muhammadiyah, Hidayatullah and others. While that does not agree generally from among those who oriented toward Saudi clerics, Salami, Persis and others. This paper discusses the proposition and the arguments of each group. In the analysis the authors, the arguments for zakat profession more rajah (strong) and assured and more meet maqashid ash-Shariah.